Influence of quadrature transformation imbalance on the noise immunity of signal reception with amplitude-phase shift keying - G. V. Kulikov; X. Kh. Dang (Российский технологический журнал)
Objectives. At the present time, amplitude-phase shift keyed (APSK) signals are actively used in satellite communication systems. In particular, they are applied in systems which operate in a limited radio frequency spectrum with increased data transmission quality requirements. Such systems use multi-channel type receivers with maximum likelihood decision on the received symbol (correlation receiver) or quadrature type receivers. The noise immunity of these receivers is directly dependent on the quality of the formation of reference oscillations. These oscillations are reference signals for correlation receivers and in-phase and quadrature components for quadrature receivers. The aim of the work is to analyze the influence of the amplitude and phase parameter spread of the in-phase and quadrature channels on the noise immunity of receiving APSK signals with a circular shape of the signal constellation.Methods. Methods of statistical radio engineering, theory of optimal signal reception, and computer simulation are used.Results. The study established the characteristics of noise immunity of the APSK signal reception depending on the spread of parameters of the quadrature converter. The theoretical calculations were confirmed by the results of modeling the transmission of APSK signals in a Gaussian communication channel. A comparison with systems using quadrature amplitude modulation (QAM) was carried out, in order to assess system stability in the presence of spread parameters among other similar systems.Conclusions. The studies enabled us to conclude that an imbalance of the quadrature reference oscillations can lead to a significant decrease in the noise immunity of radio systems using APSK signals. The minimum energy loss due to imbalance of quadrature reference oscillations is achieved when the imbalance value is less than 10% in amplitude and 2°–3° in phase. The amplitude imbalance of quadrature reference oscillations when receiving QAM signals is more pronounced than in the case of APSK signals. The phase imbalance affects approximately the same.